KONSEP AL-QUR’AN DALAM MENGHADAPI PELUANG DAN TANTANGAN ARTIFICIAL INTELLIGENCE (AI) - Tahir, Tarmizi Tarmizi; Suswandi, Suswandi (Ma'had Aly As'adiyah Sengkang, 2024)
The development of Artificial Intelligence (AI) has brought significant impacts across various aspects of life, including education, economy, and socio-culture. This technology offers great opportunities, such as increased efficiency, accessibility, and innovation in various sectors. However, on the other hand, challenges such as the loss of emotional dimensions, ethical concerns, and the potential overdependence on technology raise various moral and spiritual questions. This article aims to examine the opportunities and challenges of AI from the perspective of the Qur'an, highlighting the core values that can guide Muslims in utilizing this technology wisely. Using a thematic interpretation approach, the article explores how the Qur'an provides relevant principles to maintain a balance between technological advancement and life's blessings. The results of this study are expected to provide insights and practical solutions for the Muslim community in facing the rapid era of digital transformation. Keywords: Qur'an, Artificial Intelligence, Digital Transformation.